Cartilage and subchondral bone distributions of the distal radius: a 3-dimensional analysis using cadavers. Issue 12 (December 2020) - Miyamura, S.; Oka, K.; Lans, J.; Sakai, T.; Shiode, R.; Kazui, A.; Tanaka, H.; Shimada, S.; Murase, T.
Summary: Objective: To quantify the spatial distributions of cartilage and subchondral bone thickness of the distal radius. Design: Using 17 cadaveric wrists, three types of 3-dimensional models were created: a cartilage-bone model, obtained by laser scanning; a bone model, rescanned after dissolving the cartilage; and a subchondral bone model, obtained using computed tomography. By superimposing the bone model onto the cartilage-bone and the subchondral bone models, the cartilage and subchondral bone thickness were determined. Measurements along with the spatial distribution were made at fixed anatomic points including the scaphoid and lunate fossa, sigmoid notch and interfossal ridge, and compared at each of these four regions. Results: Cartilage thickness of the interfossal ridge (0.89 ± 0.23 mm) had a larger average thickness compared to that of the scaphoid fossa (0.70 ± 0.18 mm; p  = 0.004), lunate fossa (0.75 ± 0.17 mm; p  = 0.044) and sigmoid notch (0.64 ± 0.13 mm; p  < 0.001). Subchondral bone was found to be thickest at the scaphoid (2.18 ± 0.72 mm) and lunate fossae (1.94 ± 0.93 mm), which were both thicker than that of sigmoid notch (1.63 ± 1.06 mm: vs scaphoid fossa, p  = 0.020) or interfossal ridge (1.54 ± 0.84 mm: vs scaphoid fossa, p  = 0.004; vs lunate fossa, p  = 0.048). In the volar-ulnar sub-regions of the scaphoid and lunate fossa, the subchondral bone thickened. Conclusions: Our data can be applied when treating distal radius fractures. Cartilage thickness was less than 1 mm across the articular surface, which may give an insight into threshold for an acceptable range of step-offs. The combined findings of subchondral bone appreciate the importance of the volar-ulnar corner of the distal radius in the volar locking plate fixation.